Analisis Struktur Teks Pemberitaan Putusan Mahkamah Konstitusi Pada Akun Instagram Narasi News Room: Perspektif Analisis Wacana Kritis - Fathya, Floka Nasywa; Anshori, Dadang S.; Fu’adin, Ahmad (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
In legal reporting, especially those uploaded via digital platforms such as Instagram, there are often discrepancies in the application of journalistic language, including ineffective word choices or inappropriate sentence structures which can reduce the meaning of the legal information conveyed. This research aims to determine and analyze text structure through vocabulary and grammar contained in legal reporting on social media. In the context of media or public discourse, word choice and sentence structure function not only to convey information, but also to shape the reader's views or opinions. This research uses descriptive qualitative methods with Norman Fairclough's critical discourse analysis approach. There are three data that are analyzed and come from news about the Constitutional Court's decision in the Narasi News Room Instagram account upload. Research data is used to describe objects as they are in the hope that it can help obtain accurate information in research related to text structure analysis in Narasi News Room Instagram account uploads. The research results show that the choice of words and grammatical structure in online media reporting is very important so as not to create ambiguity in legal language.